Frese, Tobias, Wilfried E. Keil, and Kristina Krüger, eds. Sacred Scripture / Sacred Space. The Interlacing of Real Places and Conceptual Spaces in Medieval Art and Architecture. Berlin: De Gruyter, 2019 [ISBN 978-3-11-062913-2] - Fernández Martínez, Rodrigo José (Eikón / Imago, 2022)
Reseña de la obra de Frese, Tobias, Wilfried E. Keil, and Kristina Krüger, eds. Sacred Scripture / Sacred Space. The Interlacing of Real Places and Conceptual Spaces in Medieval Art and Architecture. Berlin: De Gruyter, 2019 [ISBN 978-3-11-062913-2]